2008
DOI: 10.1007/s12221-008-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of alkyl-substituted disazo yellow dyes for unmodified polypropylene fiber

Abstract: The several disazo dyes having different alkyl substituents were synthesized to dye unmodified polypropylene fiber. The affinity of the dyes onto unmodified polypropylene was increased with the increase of the length of alkyl substituents. Therefore, the heptyl-substituted dye having the longest alkyl group in this experiment showed very high color strength of dyeings with K/S value of over 24 at maximum absorption wavelength. The color fastnesses to washing, rubbing and light were also improved significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…In this procedure, the uniform mixture of dyes and dispersant (DDDMAB) was prepared. The 1 hour exposure in an ultrasonic apparatus after the addition of water to this mixture makes uniform and stable dye solution by the dispersion activity of DDDMAB [9][10][11][12][13][14][15] . This solution was finally used for dyeing.…”
Section: Preparation Of Dye Dispersionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this procedure, the uniform mixture of dyes and dispersant (DDDMAB) was prepared. The 1 hour exposure in an ultrasonic apparatus after the addition of water to this mixture makes uniform and stable dye solution by the dispersion activity of DDDMAB [9][10][11][12][13][14][15] . This solution was finally used for dyeing.…”
Section: Preparation Of Dye Dispersionsmentioning
confidence: 99%
“…The previous studies show that the dyeing of polypropylene fibers without any physical and chemical modifications is possible at the established process by super hydrophobic dyes having long alkyl substituents which impart extreme hydrophobicity to the dyes [9][10][11][12] . Anthraquinoid blue dyes were selected and investigated at first 9,10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 according to the length of alkyl substituents [4][5][6][7] . As the length of alkyl substituents increased, the dyeability toward polypropylene fiber tends to be improved dramatically for all the dyes.…”
Section: Affinity Of Alkyl-substituted Dyes Towards Polypropylenementioning
confidence: 99%
“…To have strong affinity to the hydrophobic fibers like polypropylene, dyes also need to have comparable hydrophobicity. Previous studies showed that the dyeing of polypropylene fibers without any physical and chemical modifications was possible at the established process by super hydrophobic dyes having long alkyl substituents which imparted significant hydrophobicity to the dyes [4][5][6][7] . As a successive study, logP values were calculated in order to express the hydrophobicity of the dyes numerically by a semi-empirical method using Chem3D software.…”
Section: Introductionmentioning
confidence: 99%